consider the equation f(x)=-6-1 and g(x)=4x^2 select the solution for (fg)(x)

f(x) =-6-1=-7 therefore. (fg)(x)=-7(4x^2)=-28x^2.

consider the equation f(x)=-6-1 and g(x)=4x^2 select the solution for (fg)(x)

Tutors, please sign in to answer this question.

Sandy Spring, MD

f(x) =-6-1=-7 therefore. (fg)(x)=-7(4x^2)=-28x^2.

Westford, MA

(fg)(x) = f(x) * g(x) = (-6-1) * (4x^2) = -28x^2

- Calculus 2207
- Math Help 5453
- Algebra 2 3504
- Algebra 1 4080
- Geometry 1907
- Precalculus 1595
- Trigonometry 1526
- Prealgebra 172
- Math 9889
- Physics 2183